2021
DOI: 10.1057/s41599-021-00870-2
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between partisanship, forecasted COVID-19 deaths, and support for preventive policies

Abstract: The COVID-19 pandemic is a global crisis that has forced governments around the world to implement large-scale interventions such as school closures and national lockdowns. Previous research has shown that partisanship plays a major role in explaining public attitudes towards these policies and beliefs about the intensity of the crisis. However, it remains unclear whether and how partisan differences in policy support relate to partisan gaps in beliefs about the number of deaths that the pandemic will cause. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Interpersonal trust is vital: avoiding the spread of the virus depends not only on our own behavior, but also on the behavior of other’s – particularly as countries reopen and people interact more with each other outside of their COVID-19 “bubbles”. Moreover, trusting communication by governmental authorities is also important as partisanship matters for the spread of the virus [ 23 , 25 ]. On this front, the Latin American countries covered by this survey present a challenging backdrop.…”
Section: Resultsmentioning
confidence: 99%
“…Interpersonal trust is vital: avoiding the spread of the virus depends not only on our own behavior, but also on the behavior of other’s – particularly as countries reopen and people interact more with each other outside of their COVID-19 “bubbles”. Moreover, trusting communication by governmental authorities is also important as partisanship matters for the spread of the virus [ 23 , 25 ]. On this front, the Latin American countries covered by this survey present a challenging backdrop.…”
Section: Resultsmentioning
confidence: 99%
“…Even if diverse preventive measures that have been found to be effective are planned and implemented by agents, without people's compliance with the measures, successful control of the pandemic could not be achieved [6]. For instance, rejection of and noncompliance with the recommended and required preventive measures associated with political debates resulted in the recent drastic increase in COVID-19 cases and deaths caused by the Delta variant in multiple countries across the globe [5,7]. Hence, it would be important to understand which factors are involved in people's compliance as well as noncompliance with preventive measures.…”
Section: Introductionmentioning
confidence: 99%
“…However, psychological distress was also elevated during that period ( Torrente et al, 2021 , 2022 ). Furthermore, political ideology influenced citizen support for restrictions in Argentina even more than public health concerns ( Freira et al, 2021 ) as was the case in other countries such as the United States ( Grossman et al, 2020 ; Clinton et al, 2021 ). Therefore, the announcement of new restrictions could be a driver for greater political polarization with the consequence of less support and erosion of the effectiveness of health measures.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that messages that heighten risk appraisals change intentions and behaviors related to health protection and safety in different domains, such as vaccination, dieting, dental hygiene, sun protection, driving, or medical testing ( Sheeran et al, 2014 ). However, the acceptance of government restrictions is plausibly a different kind of health behavior, more heavily influenced by factors distinct from risk perception, like ideology and trust ( Freira et al, 2021 ). Considering these differences with other health behaviors, it could be of interest to know if acceptance of restrictions could be modulated also by messages that heighten risk appraisals.…”
Section: Introductionmentioning
confidence: 99%